Advanced Ceramic Materials (IntechOpen, 2023)
This book examines exciting advancements in the field of ceramics, including nanotechnology, clean energy, and tribology as well as fundamental concepts like defects and structure. It is a comprehensive discussion on how today’s ceramics are processed and used in many of today’s critical technologies. It discusses current techniques for synthesizing durable and cost-effective ceramic components with biocompatibility, complexity, and high precision. This book is a comprehensive reference for researchers, engineers, dental clinicians, biologists, academics, and students interested in ceramics.